2018
DOI: 10.3892/or.2018.6463
|View full text |Cite
|
Sign up to set email alerts
|

miR‑1 inhibits the progression of colon cancer by regulating the expression of vascular endothelial growth factor

Abstract: MicroRNA (miR)-1 is associated with various human malignancies through repressing tumor growth, migration and angiogenesis. Recently, high-throughput transcriptional profiling confirmed that miR-1 is markedly downregulated in metastatic colorectal cancer; however, its biological functions and the specific underlying mechanisms in colorectal cancer (CRC) require further investigation. In this study, the expression of miR-1 in 111 CRC and paired normal tissue samples was measured using quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…miR-1-3p expression shows negative correlation with tumour size, degree of differentiation, lymph node metastasis and tumour/nodus/metastasis stage (TNM) [ 85 , 86 , 87 ]. In vitro, miR-1-3p suppresses cell growth, migration, motility and glycolysis by targeting VEGF [ 87 ] and notch receptor 3 ( NOTCH3 ), which is known to be crucially involved in developmental processes by controlling cell fate decisions [ 88 ] as well as hypoxia-inducible factor 1 subunit alpha ( HIF1A ) [ 89 ]. The target genes of miR-1-3p also encode for NLR family apoptosis inhibitory protein ( NAIP ), which plays a role in the inhibition of apoptosis [ 86 ], and the focal adhesion protein LIM and SH3 protein 1 ( LASP1 ) [ 85 ].…”
Section: Mirna Clusters Down-regulated In Human Crcmentioning
confidence: 99%
“…miR-1-3p expression shows negative correlation with tumour size, degree of differentiation, lymph node metastasis and tumour/nodus/metastasis stage (TNM) [ 85 , 86 , 87 ]. In vitro, miR-1-3p suppresses cell growth, migration, motility and glycolysis by targeting VEGF [ 87 ] and notch receptor 3 ( NOTCH3 ), which is known to be crucially involved in developmental processes by controlling cell fate decisions [ 88 ] as well as hypoxia-inducible factor 1 subunit alpha ( HIF1A ) [ 89 ]. The target genes of miR-1-3p also encode for NLR family apoptosis inhibitory protein ( NAIP ), which plays a role in the inhibition of apoptosis [ 86 ], and the focal adhesion protein LIM and SH3 protein 1 ( LASP1 ) [ 85 ].…”
Section: Mirna Clusters Down-regulated In Human Crcmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small non-coding RNA molecules of 20-22 nucleotides, which can directly bind to the 3′-untranslated region (3′-UTR) of target gene mRNAs to inhibit their translation (3). Increasing studies have reported that patients with tumor exist in a variety of disorders and abnormal expression of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In infectious rat lung work involving the nematode Angiostrongylus cantonensis , a pathogenic species causing eosinophilic meningitis in humans, the miR-1 expression level significantly increases during the infectious stage from larvae to young adults, and is the highest expressed miRNA in A. cantonensis during its parasitic cycle. Furthermore, the miR-1 is dysregulated in various cancers as a tumor-suppressive miRNA that targets multiple genes [25,26]. Overexpression of miR-1 is associated with increased chemosensitivity to anticancer drugs [27], and the downregulation of miR-1 is associated with the exposure to carcinogenic agents [28].…”
Section: Discussionmentioning
confidence: 99%